Optogenetic Monitoring of Synaptic Activity with Genetically Encoded Voltage Indicators - Nakajima, Ryuichi; Jung, Arong; Yoon, Bong-June; Baker, Bradley J. (Frontiers in Synaptic Neuroscience, 2016)
The age of genetically encoded voltage indicators has matured to the point that changes in membrane potential can now be observed optically in vivo. Improving the signal size and speed of these voltage sensors has been the primary driving forces during this maturation process. As a result, there is a wide range of probes using different voltage detecting mechanisms and fluorescent reporters. As the use of these probes transitions from optically reporting membrane potential in single, cultured cells to imaging populations of cells in slice and/or in vivo, a new challenge emerges – optically resolving the different types of neuronal activity. While improvements in speed and signal size are still needed, optimizing the voltage range and the subcellular expression (ie., soma only) of the probe are becoming more important. In this review, we will examine the ability of recently developed probes to report synaptic activity in slice and in vivo. The VSFP family of voltage sensors, ArcLight, ASAP-1, and the rhodopsin family of probes are all good at reporting changes in membrane potential, but all have difficulty distinguishing subthreshold depolarizations from action potentials and detecting neuronal inhibition when imaging populations of cells. Finally, we will offer a few possible ways to improve the optical resolution of the various types of neuronal activities.